A home at trail's end ebook - Carlson, Melody A. (Homeward on the Oregon Trail, 2013)
Bestselling author Melody Carlson (more than 5 million books sold) continues her Homeward on the Oregon Trail series with this third and final adventure. Elizabeth Martin and her two children have finally reached the Oregon Country. But Eli Kincade, the wagon train scout who captured her heart, has chosen to continue life on the trail. As other pioneer families begin building new homes, Elizabeth has never felt more alone. However, when Eli unexpectedly returns, confesses his love, and proposes, Elizabeth accepts with her family's blessing. A community begins to take shape, but not without growing pains. As an alternative to the local minister's fiery sermons, Elizabeth's father begins to preach at home, raising the ire of some. Racial biases arise against Brady, Elizabeth's African-American hired hand. Eli's warm sentiments toward Indians also raises concerns. Can Elizabeth and her family overcome these differences and begin a legacy of reconciliation and love? About This Series: The Homeward on the Oregon Trail series brings to life the challenges a young widow faces as she journeys west, settles her family in the Pacific Northwest, and helps create a new community among strong-willed and diverse pioneers.